A oralidade esquizofrênica - Pereira, Thaís da Silva (2015)
This dissertation aims to investigate the manifestation of orality and its implications in schizophrenia. The main question of the research is what orality was found in schizophrenia? In this case, a schizophrenic patient expresses its pathos also through orality, to ingest objects, especially metals. Through research were traced ideas on how the meeting between schizophrenia and orality occurs. From the concept of schizophrenic orality, it is possible to think of the originality of schizophrenia and its implications on their way of being in the world, creatively and destructively. It is thought in a mouth-body, which features a mangling on the body schema, making it without representation. The schizophrenic orality consists initially in the first oral phase where the person was a receptacle of partial objects; being that, it does not become possible to make the necessary path for the total objects and differentiation with each other. So the schizophrenic ends up relating in a disintegrated way with the objects of the world and with others, including the schizophrenic orality. The clinician while attending schizophrenic patients should consider schizophrenic orality because it is a manifestation that says a lot about the pathos, with a possible opening for creativity on clinical activity aiming a lower destructiveness in these patients